Insects as biological models to assay spider and scorpion venom toxicity - Manzoli-palma, M. F. [UNESP]; Gobbi, N. [UNESP]; Palma, M. S. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2003)
This study was undertaken to develop an experimental protocol using insects as biological models to assay venom toxicity of the following spiders Loxosceles gaucho, Phoneutria nigriventer, Nephilengys cruentata and Tityus serrulatus scorpion. Three different insect species were bioassayed: Apis mellifera (Hymenoptera), Grillus assimilis (Orthoptera), and Diatraea saccharalis (Lepidoptera). Venoms were injected into the hemocele of insects with a microsyringe at concentrations that caused dose/weight-dependent effects; doses causing either paralysis (ED50) or death (LD50) were recorded for each venom and insect test-species. T. serrulatus and L. gaucho venoms were lethal to all tested species, while P. nigriventer venom caused paralysis and death, and N. cruentata venom caused only paralysis at the doses assayed. A comparison between the insect test species described above revealed that A. mellifera was highly sensitive to all venoms tested; even a tiny amount of N. cruentata non-lethal venom caused a change in the walking pattern leading to transient paralysis. D. saccharalis larvae were very resistant to all four venoms.
Keywords: bioassay; venom; insect model; toxicity; Apis mellifera